Incidence of Surgical Site Infection and Factors Associated among Cesarean Deliveries in Selected Government Hospitals in Addis Ababa, Ethiopia, 2019 - Hana Lijaemiro; Semarya Berhe Lemlem; Jembere Tesfaye Deressa (Obstetrics and Gynecology International)
Background. One-third to two-thirds of operated patients in low-income countries acquire surgical site infection, which is nine times higher when compared to high-resource countries. Identifying the incidence and risk factors that contribute to surgical site infection following cesarean delivery is a step ahead for preventing and reducing the problem. Nonetheless, the distribution of the problem in Addis Ababa, where the rate of cesarean delivery is relatively high compared to other parts of the country, is under investigation. Objective. The aim of this study is to assess the incidence of surgical site infection among cesarean deliveries and factors associated with it in selected governmental hospitals found in Addis Ababa, Ethiopia, in 2019. Method. A hospital-based prospective cohort study design was employed to follow 175 women, who gave birth by cesarean delivery in selected government hospitals in Addis Ababa, from March 11 to April 9, 2019. Convenience sampling method was used to select study units from the randomly selected hospitals. Descriptive statistics were run for determining the rate of cesarean delivery surgical site infection. Presence and degree of association between outcome and independent variables were computed through bivariate logistic regression analysis and factors that had p<0.2 significance level in the bivariate logistic regression analysis were considered in the multivariable logistic regression analysis. Result. From 166 participants who completed 30-day follow-up, 25 (15%) of the participants developed surgical site infection. Age, gestational age, duration of operation, and ≥5 vaginal examinations showed a significant association with the outcome variable with AOR (95% CI) of ((AOR = 1.504, 95% CI: (1.170 – 1.933, p=0.001))), ((AOR = 0.019, 95% CI: (0.001 – 0.291, p=0.004))), ((AOR = 1.108, 95% CI: (1.025 – 1.197, p=0.009))), and ((AOR = 13.076, 95% CI: (1.018 – 168.002, p=0.048))), respectively. Conclusion and recommendation. Surgical site infection rate is higher and certain associations lost due to small sample size. Further interventional studies with vast sample size are recommended.